A Highly Reactive Geminal P/B Frustrated Lewis Pair: Expanding the Scope to C−X (X=Cl, Br) Bond Activation. Issue 10 (2nd February 2016) - Samigullin, Kamil; Georg, Isabelle; Bolte, Michael; Lerner, Hans‐Wolfram; Wagner, Matthias
Abstract: The geminal frustrated Lewis pair t Bu2 PCH2 B(Fxyl)2 (1 ; Fxyl=3, 5‐(CF3 )2 C6 H3 ) is accessible in 65 % yield from t Bu2 PCH2 Li and (Fxyl)2 BF. According to NMR spectroscopy and X‐ray crystallography, 1 is monomeric both in solution and in the solid state. The intramolecular P⋅⋅⋅ B distance of 2.900(5) Å and the full planarity of the borane site exclude any significant P/B interaction. Compound1 readily activates a broad variety of substrates including H2, EtMe2 SiH, CO2 /CS2, Ph2 CO, and H3 CCN. Terminal alkynes react with heterolysis of the C−H bond. Haloboranes give cyclic adducts with strong P−BX3 and weak R3 B−X bonds. Unprecedented transformations leading to zwitterionic XP/BCX3 adducts occur on treatment of1 with CCl4 or CBr4 in Et2 O. In less polar solvents (C6 H6, n ‐pentane), XP/BCX3 adduct formation is accompanied by the generation of significant amounts of XP/BX adducts. FLP1 catalyzes the hydrogenation of PhCH=N t Bu and the hydrosilylation of Ph2 CO with EtMe2 SiH. Abstract : Complementary twins : The geminal frustrated Lewis pair t Bu2 PCH2 B[3, 5‐(CF3 )2 C6 H3 ]2 (1 ) is accessible from t Bu2 PCH2 Li and [3, 5‐(CF3 )2 C6 H3 ]2 BF. Compound1 readily activates element–element single, double, and triple bonds. Remarkably, CX4 undergoes C−X bond heterolysis with formation of unprecedented XP/BCX3 adducts (X=Cl, Br; see scheme).